Respuesta :
Answer:
x2 + x - 20.
Step-by-step explanation:
(x-4)(x+5) = x^2-4x+5x-20 = x^2+x-20 = x^2 + x - 20.
Hope This Helped
[tex]\mathbb{PROBLEM :}[/tex]
[tex] \tt \: 6. Multiply: ( \times - 4)(x + 5)[/tex]
==========================================
[tex]\mathbb{ANSWER:}[/tex]
[tex] \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \tt \underline \color{green}{x2 + x - 20}[/tex]
==========================================
[tex]\mathbb{SOLUTION:}[/tex]
[tex] \: \: \: \: \: \: \: \: \tt( \times - 4)( \times + 5)[/tex]
[tex] \: \: \: \: \: \: \: \: \tt = \: x(x + 5) -4(x + 5)[/tex]
[tex] \: \: \: \: \: \: \: \: \tt{ = \times 2 + 5 \times 4 \times - 20}[/tex]
[tex] \: \: \: \: \: \: \: \: \tt{= x2 + x - 20}[/tex]
[tex] \tt \: So \: possible \: Answer \: is : \underline \green{ \times 2 + \times - 20}[/tex]
==========================================
┌─────── ∘°❁°∘ ───────┐
︎ CarryOnLearning ૮₍˶ᵔ ᵕ ᵔ˶₎ა
︎︎└─────── °∘❁∘° ───────┘